The impacts of relationship marketing orientation on relational response behaviours - Sayil, Emine Mediha; Donmaz, Aysegul; Simsek, Gulhayat Golbasi; Akyol, Ayse (INDERSCIENCE ENTERPRISES LTD, 2016)
This study aims to investigate the direct and indirect impacts of relationship marketing orientation (RMO) components - trust, competency, commitment, communication and conflict handling - on customers' relational response behaviours, such as satisfaction, loyalty, and positive word of mouth (WOM), in the Turkish mobile telecommunications industry. A total of 230 usable questionnaires were collected in Istanbul, Turkey, in August 2013 using convenience sampling. After confirmation of the measurement model, the direct and indirect effects of RMO components on customers' relational response behaviours were analyzed using path analysis and the product of path coefficients. The findings show that all the RMO components, except competency, have significant positive impacts on relational response behaviours. Of all the RMO components, trust has the strongest positive impact on satisfaction and positive WOM, whereas conflict handling has the strongest positive impact on loyalty. In addition, of all the variables, satisfaction has the strongest direct impact on loyalty, and loyalty has the strongest direct impact on positive WOM in Turkey's mobile telecommunications industry.
Keywords: commitment; communication; competency; conflict handling; loyalty; positive word of mouth; relationship marketing orientation; satisfaction; trust; Turkish mobile telecommunication; MOBILE SERVICE INDUSTRY; CUSTOMER LOYALTY; PERCEIVED VALUE; QUALITY